PELAKSANAAN SANKSI ADAT BAGI PELAKU ZINA DI KECAMATAN SELUMA UTARA KABUPATEN SELUMA PERSPEKTIF HUKUM ISLAM - Suparlan, Elon (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This study  discusses  the  implementation of the  determination of Integrated  Marriage  of The  formulation of this research  are:  Firstly, how  is the society’s response to the enactment of Government Regulation  No. 19 of 2015  on Non-Tax State  Revenue in the  Ministry of Religious Affairs? Second, what  factors cause  the  community to carry out  marriage  in the Central  Marriage on KUA Kecamatan Ratu Agung?The  type of this research  is descriptive  research  with sociological juridical approach. Data collection using interview technique, observation, documentation. This study concludes  that: Firstly, the public welcomes  a positive response to the enactment of Government Regulation  No. 19 of 2015.  The regulation  is considered as the government’s new breakthrough to discipline the marriage  cost so as to minimize illegal levies. In addition, people  with limited economic ability who want to get married  is greatly helped  by the existence  of this provision.  If previously the cost of marriage is felt by them is quite high, with this provision they can perform the marriage  for free with the condition must be implemented in the Office of Religious Affairs and  at work hours.  Of course  this gets a positive response from the community, because it is very helpful especially for the middle to lower society. Secondly,  the factors that cause  the community to carry out marriage  in the marriage  hall at the Office of Religious Affairs of Ratu Agung District are economic factors and  work permits.  In general, informants  stated  that getting married  in the Office of Religious Affairs without  cost so as to ease  the financial burden. In ad- dition,  the informant  was married  in the Office of Religious Affairs of Ratu Agung Sub-district  due  to the reason  of the work permit which was not long